PERAN KOMISI INFORMASI PUBLIK DALAM PROSES EKSEKUSI TERHADAP PUTUSAN SENGKETA INFORMASI YANG BERKEKUATAN HUKUM TETAP DALAM TINJAUAN UU NO.14 TAHUN 2008 TENTANG KETERBUKAAN INFORMASI PUBLIK - Slamet Haryanto; Kadi Sukarna (Universitas Semarang, 2017)
The community as the users of information has sufficiently important rights in the context of information disclosure. When the right to obtain information isinhibited because the public entity or governor is not available in the execution ofthe information disclosure management, then public information lawsuit willemerge in the implementation of the public information disclosure. The public information lawsuit happens when public entity and the user ofinformation disputes with something related to the rights to acquire informationand to use information based on legislation. The completion of the lawsuitthrough nonlitigation ajudication is the process of the completion of publicinformation lawsuit. The completion of the information through nonlitigationajudication is hopefully able to resolve the dispute fast, low cost, and simple. The problems in this thesis are: a) how the mechanisms of the settlement ofpublic information lawsuit in the Information Commission, b) what obstacles andsolutions of the execution implementation of the Information Commissiondecisions which have been legally binding. Answering the problem, research with juridical normative approach methodwith analytical descriptive research specification was conducted. The type of dataused in this study is secondary data. Based on the research that had been conducted, it was found that PublicInformation Lawsuit Settlement Procedure, the execution of the decision or theexecution of the Information Commission decision which had been legallybinding was conducted by the competent Court, in the context that the publicinformation lawsuit settlement was the court within the jurisdiction of the pleated.In this case if the pleated is State or Government public entity then the court inquestion is the Administrative Court of the State, whereas if the execution pleated is a party outside the State or Government public entity then the competent court is the competent District Court. The execution authority of the Information Commission decision granted tothe State Administrative Court as well as the District Court, causes theinformation users to experience the long process of obtaining information whichis their needs or constitutional rights.